Analysis Of Agroforestry Farmers’ Income Level Based On Planting Patterns In Negeri Leahari, South Leitimur District, Ambon City - Sahureka, Mersiana; WATTIMENA, CORNELIA M.A. (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
The agroforestry system is a form of optimal land use that is oriented towards production as well as protecting land resources. The agroforestry production system has the peculiarity of producing more than one type of product. Research aims: 1). Knowing patterns in agroforestry management, 2). Analyzing farmers' income levels based on cropping patterns. This research uses direct observation methods and interviews with the community. The results of the research show that the response characteristics which include: age level, education level, hamlet area, distance from house to hamlet have a very positive influence on the income obtained from the agroforestry pattern. The highest level of income is type III with the main crop types namely cloves, nutmeg and durian while the supporting crop types are langsat, duku, cassava and chilies with an income level of IDR 102,325,000 while the lowest income is IDR 16,300,000, namely type V with the composition of plant types. The main ones are cloves, coconut and cassava, the composition of supporting plant types is durian, sago banana and chilies